THE EFFECT OF INSTITUTIONAL OWNERSHIP, MANAGERIAL OWNERSHIP, COMPANY GROWTH AND CASH HOLDING ON FIRM VALUE - Kelvin Caesar Julian Sihite; Niken Wahyu Cahyaningtyas; Ira Maya Hapsari (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Analysis of the impact of financial ratios on firm value in infrastructure sector companies going public in 2020–2024 is the goal of this study. The following factors affect company value: cash holdings, company growth, managerial ownership, and institutional ownership. To get 105 samples that satisfy the requirements across the 2020–2024 timeframe, a quantitative research approach using purposive sampling is employed. Using SPSS, multiple linear regression analysis is the data analysis method employed. The results of the study indicate that institutional ownership, business expansion, and cash holdings have a greater impact on firm value than managerial ownership. In addition, the value of a firm is affected by cash holdings, company expansion, managerial ownership, and institutional ownership. Keywords: Cash Holding; Company Growth; Managerial Ownership; Institutional Ownership; Firm Value